Pelatihan Pemanfaatan Multimedia Pembelajaran Berbasis Android sebagai Sumber Belajar Anak Usia Sekolah di Desa Poowo Barat, Kecamatan Kabila - Ritin Uloli; Nova Elysia Ntobuo (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
The development of information and communication technology has opened opportunities for using digital devices as flexible and engaging learning resources for school-age children. However, Android-based smartphone ownership among children in Poowo Barat Village, Kabila Subdistrict, remains oriented more towards entertainment than learning activities due to limited knowledge of suitable educational applications. This community service program aims to improve the knowledge, skills, and motivation of school-age children in utilizing Android-based multimedia learning as an effective learning resource. The program was implemented through a participatory training and mentoring approach across three stages: preparation, implementation (socialization, demonstration, and hands-on practice), and evaluation using observation sheets and questionnaire. The results showed an improvement in participants' knowledge and skills in accessing, selecting, and operating Android-based learning applications. The program contributed to strengthening digital literacy and fostering independent learning habits among school-age children. It is concluded that training in the use of Android-based multimedia learning is an effective strategy for strengthening technology-based learning resources at the community level.